2009
DOI: 10.1021/pr900565b
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Adult Germline Stem Cells and Embryonic Stem Cells: Comparative Proteomic Approach

Abstract: Spermatogonial stem cells isolated from the adult mouse testis acquire under certain culture conditions pluripotency and become so-called multipotent adult germline stem cells (maGSCs). They can be differentiated into somatic cells of the three germ layers. We investigated a subset of the maGSCs and ESCs proteomes using cell lines derived from two different mouse strains, narrow range immobilized pH gradients to favor the detection of less abundant proteins, and DIGE to ensure confident comparison between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 45 publications
1
33
0
7
Order By: Relevance
“…Because of the high proteome similarity between the maGSCs and ESCs, 13 DIGE analysis of the cell extracts from the two cell types stimulated with RA was performed. The achieved DIGEgels of the stimulated cells indicated a significant difference in protein pattern, showing that 55 protein spot were differently expressed, when maGSCs/RA was compared to ESCs/RA (Supplemental Figure 1).…”
Section: Comparative Analysis Of the Proteome Of The Differentiated Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high proteome similarity between the maGSCs and ESCs, 13 DIGE analysis of the cell extracts from the two cell types stimulated with RA was performed. The achieved DIGEgels of the stimulated cells indicated a significant difference in protein pattern, showing that 55 protein spot were differently expressed, when maGSCs/RA was compared to ESCs/RA (Supplemental Figure 1).…”
Section: Comparative Analysis Of the Proteome Of The Differentiated Mmentioning
confidence: 99%
“…We confirmed on the proteome level the ESC-like nature of maGSCs. 13 To identify new potential pluripotence correlated proteins or differentiation associated proteins, we investigated the effects of retinoic acid (RA) treatment on the protein expression profiles of maGSCs and ESCs and identified proteins potentially involved in the SCs differentiation. We demonstrated the important role of Eif5a in stem cell differentiation and highlighted the role of the hypusination as a stem cell differentiation and cell cycle control step.…”
Section: ' Introductionmentioning
confidence: 99%
“…mGSCs from adult mouse testis, so-called multipotent adult germline stem cells (maGSCs) were firstly isolated and described by our group. It was recently shown that maGSCs and ESCs express the same clusters of microRNAs (miRNAs; Zovoilis et al, 2008) previously thought to be ESC-specific (Houbaviy et al, 2003) and also share the same proteomic profiles (Dihazi et al, 2009). More recently, another study described similarities between maGSCs and ESCs at the epigenetic level by investigating the DNA methylation status of several imprinted genes, pluripotency marker genes as well as global DNA methylation patterns in the undifferentiated and differentiated state (Zechner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, protein chloroform/methanol precipitation was carried out according to Wessel and Flugge [23] and protein estimation was performed using the Bio-Rad protein assay according to Bradford [24] . 2-DE and DIGE-analyses were carried out as previously described [25] .…”
Section: D Gel Electrophoresismentioning
confidence: 99%